2018
DOI: 10.32404/rean.v5i4.3142
|View full text |Cite
|
Sign up to set email alerts
|

RATES OF APPLICATION OF Azospirillum brasilense IN TOMATO CROP

Abstract: The use of plant growth-promoting bacteria (PGPB) may be a promising agronomic practice to improve the growth and productivity of vegetables. The objective of this work was to evaluate the effect of inoculation of Azospirillum brasilense on plant growth and tomato fruit production. Two experiments were carried out: the first one evaluating the growth of the plants in a greenhouse and the second one evaluating the production of fruits under field conditions. The experimental design used in two experiments was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Revolti (2014) [14] and Pereira et al (2015) [15], studied the influence of genotypes on the inoculation of A. brasilense and concluded that the response to inoculation varies according to the genotypes used, that is, hybrids influence the response to inoculation. Researchers such as Bárbaro et al (2008) [16] indicate the possibility of selecting strains suitable for local soil and climate conditions, as well as the crops and their cultivars used in each region [17][18][19][20] In this test, garlic bulbs treated with Azospirillum brasilense showed a significant increase in diameter, bulb weight and root weight. Evidence has shown that this alpha-proteobacterium stimulates garlic bulbs already at the time of transplantation ensuring a higher water supply and an increase in the solubilization of minerals present in the substrate and in the soil [21][22], in particular iron/phosphorus and the synthesis of hormones such as GA and IAA, influencing many processes beneficial for the plant: in particular a greater resistance to biotic and abiotic stress (salt and water stress) and a better preservation of the product, with a higher content of vitamins B1, B3, B5.…”
Section: Discussionmentioning
confidence: 99%
“…Revolti (2014) [14] and Pereira et al (2015) [15], studied the influence of genotypes on the inoculation of A. brasilense and concluded that the response to inoculation varies according to the genotypes used, that is, hybrids influence the response to inoculation. Researchers such as Bárbaro et al (2008) [16] indicate the possibility of selecting strains suitable for local soil and climate conditions, as well as the crops and their cultivars used in each region [17][18][19][20] In this test, garlic bulbs treated with Azospirillum brasilense showed a significant increase in diameter, bulb weight and root weight. Evidence has shown that this alpha-proteobacterium stimulates garlic bulbs already at the time of transplantation ensuring a higher water supply and an increase in the solubilization of minerals present in the substrate and in the soil [21][22], in particular iron/phosphorus and the synthesis of hormones such as GA and IAA, influencing many processes beneficial for the plant: in particular a greater resistance to biotic and abiotic stress (salt and water stress) and a better preservation of the product, with a higher content of vitamins B1, B3, B5.…”
Section: Discussionmentioning
confidence: 99%
“…Tomatoes may respond to inoculation with Azospirillum (Alfonso et al 2005; Mangmang et al 2015a; Lima et al 2018). In Colombia, inoculation with A. brasilense resulted in better seedling growth, plant nutritional status, and yield 11% higher than the non-inoculated control (Alfonso et al 2005) (Table 1).…”
Section: Main Inoculated Cropsmentioning
confidence: 99%
“…For tomato, it is verified that the inoculation of plants with A. brasilense improves the physiological activities of photosynthesis, accumulation of pigments, and antioxidant compounds (Lade et al, 2018;Pérez-Rodriguez et al, 2020). These changes increase vegetative development, yield (Escalante et al, 2015;Esquivel-Cote et al, 2017;Lima et al, 2018), and quality of the fruits (Caradonia et al, 2020). Many results are related to the higher production of phytohormones, emphasizing abscisic acid, atmospheric N fixation, and P solubilization (Mangmang et al, 2015b;Pereg et al, 2016;Dudás et al, 2017).…”
Section: Flowers and Fruitsmentioning
confidence: 95%